Gene expression study of candidate Arabidopsis defence genes in response to the bacterial wilt pathogen, Ralstonia solanacearum - Berger, David Kenneth (University of Pretoria, 2024)
Dissertation (MSc (Biotechnology))--University of Pretoria, 2015.